2014
DOI: 10.1002/pbc.25068
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of eculizumab in children and adolescents with paroxysmal nocturnal hemoglobinuria

Abstract: Eculizumab appears to be a safe and effective therapy for children with PNH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 42 publications
(105 reference statements)
1
29
0
4
Order By: Relevance
“…Recently, a complement inhibition therapy using eculizumab, a humanized anti-C5 monoclonal antibody, has been shown to have beneficial effects for treatment of paroxysmal nocturnal hemoglobinuria and atypical hemolytic uremic syndrome in which complement-mediated damages take place [31,32]. Furthermore, it has been suggested that eculizumab might be effective in neuromyelitis optica [33], in intractable thrombotic microangiopathy associated with SLE [34] and in severe resistant LN [35].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a complement inhibition therapy using eculizumab, a humanized anti-C5 monoclonal antibody, has been shown to have beneficial effects for treatment of paroxysmal nocturnal hemoglobinuria and atypical hemolytic uremic syndrome in which complement-mediated damages take place [31,32]. Furthermore, it has been suggested that eculizumab might be effective in neuromyelitis optica [33], in intractable thrombotic microangiopathy associated with SLE [34] and in severe resistant LN [35].…”
Section: Discussionmentioning
confidence: 98%
“…В настоящее время подходы к тера-пии изменились. Таргетная терапия моноклональны-ми антителами к С5-компоненту комплемента (эку-лизумабом) приводит к значительному уменьшению или полному подавлению гемолиза и предотвраще-нию жизнеугрожающих осложнений у пациентов с ПНГ [1,3,10]. Таким образом, на современном эта-пе диагноз ПНГ не рассматривается как показание для проведения ТКМ.…”
Section: заключениеunclassified
“…Таким образом, на современном эта-пе диагноз ПНГ не рассматривается как показание для проведения ТКМ. В то же время экулизумаб не влияет на цитопению, связанную с сопутствуюшей недостаточностью костного мозга, поэтому ТКМ проводится в рамках стандартных показаний при аплазии кроветворения или в редких случаях транс-формации ПНГ в миелодиспластический синдром/ острый лейкоз [1,3,10].…”
Section: заключениеunclassified
See 1 more Smart Citation
“…К л и н и ч е с к и е н а б л ю д е н и я рата в лечении ПНГ, в том числе у детей, установлены в двойных слепых, плацебоконтролируемых исследо-ваниях и длительных наблюдательных исследованиях [15,16]. У обоих наших пациентов лечение экули-зумабом привело к быстрому восстановлению содер-жания гемоглобина и ликвидации признаков гемо-лиза, причем во втором наблюдении эффект препарата был отмечен уже после 1-й инфузии пре-парата.…”
unclassified